Holocaust and human rights education : good choices and sociological perspectives - Polgar, Michael (Emerald Publishing Limited, 2018)
Educators and students face many questions when exploring the history of the Holocaust. Both the harrowing historical narrative and its wider contemporary implications make the Holocaust an essential part of our education, whilst simultaneously bringing to the fore challenging questions of how best to recount such an event.This book addresses these crucial questions by exploring the way in which we teach and learn about the Holocaust. It demonstrates how we can dignify memories of the Holocaust by joining with resilient survivors, as well as how careful discussion and interpretation of definitions and appropriate representations can link the Holocaust to human rights and international law. It also highlights that understanding the Holocaust serves as a catalyst for the expansion of human rights and for genocide prevention. Throughout, Polgar applies sociological concepts that can help all of us to understand how the Holocaust has become both a particular concern for Jewish and European groups and also a basis for laws and practices that support universal human rights. Advocating for the inclusion of the Holocaust in multicultural education, this text will prove invaluable to students, researchers and educators alike.
Keywords: Holocaust, Jewish (1939-1945) -- Study and teaching -- Social aspects.; Human rights -- Study and teaching -- Social aspects.; Education -- Multicultural Education.; Multicultural education.; elektronické knihy; electronic books